Brazilian food - Castanho, Thiago (New York : Firefly Books Ltd, 2014)
"In this book ... chefs explore the best of Brazilian food and its traditions. Through 100 recipes for everythin from street food to seafood, sweet treats to cokctails, you can discover the authentic flavours of Brazil-wherever you live"
My Brazilian cuisine -- A family story -- What is Brazilian food? -- Small bites and drinks -- Street food -- Vegetables from field and forest -- Side dishes -- From river and sea -- Meat and poultry for fire and grill -- Bread -- Sweet treats -- Key ingredients.
Includes index.
Keywords: COOKING, BRAZILIAN